2015
DOI: 10.1002/2014wr015745
|View full text |Cite
|
Sign up to set email alerts
|

A method for characterizing desiccation-induced consolidation and permeability loss of organic soils

Abstract: A new method was developed to measure soil consolidation by capillary suction in organic soils. This method differs from previous methods of measuring soil consolidation in that no external load is utilized and only the forces generated via capillary suction consolidate the soil matrix. This limits the degree of consolidation that can occur, but gives a more realistic ecological perspective on the response of organic soils to desiccation in the field. This new method combines the principles behind a traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…16 From a soil physical perspective, extreme drying can physically alter the structure of soil material such that flow and storage properties are irreversibly altered. [19][20][21] These changes can be manifested through crack formation, 20 increases in macroporosity, 21 lowered storage capacity, 18 and greater preferential flow. 22 Alternatively, it has been suggested that CO2 enrichment may drive increases in root exudation and mycorrhizae activity which convey greater soil aggregate stability 23 and more water retention in finer pores.…”
Section: Introductionmentioning
confidence: 99%
“…16 From a soil physical perspective, extreme drying can physically alter the structure of soil material such that flow and storage properties are irreversibly altered. [19][20][21] These changes can be manifested through crack formation, 20 increases in macroporosity, 21 lowered storage capacity, 18 and greater preferential flow. 22 Alternatively, it has been suggested that CO2 enrichment may drive increases in root exudation and mycorrhizae activity which convey greater soil aggregate stability 23 and more water retention in finer pores.…”
Section: Introductionmentioning
confidence: 99%
“…Shrinkage refers to the loss of volume occupied by the water (through vertical and horizontal drainage and evapotranspiration) and rearrangement of the particles (including compaction) when the water is removed (Arnold & Ghezzehei 2015, Ilnicki 2002, Oleszczuk et al 2003). …”
Section: Role Of Water Loss In Subsidence Of Dredged Sediment Drainagmentioning
confidence: 99%